El Gabinete de lectura del Ateneo Mexicano - López Zahar, Jocelyn Guadalupe (2021)
The Ateneo Mexicano, one of the first literary society in independent Mexico, was created to promote public education in that young country. The institution had its own Reading Cabinet. An inventory of books donated to the National Museum of Mexico shows that what kind of printed materials use to had the Ateneo’s library. That inventory was reconstructed and is presented in this article to reveal an important source of information, it shows the thematic variety of books, concerning with all topics of the classes given by Ateneo’s members.